A co-construção de práticas pedagógicas decoloniais na formação de educadoras/es que atuam com pessoas LGBTQIAP+ no projeto Casa 1 - Fiorotti, Victor Fernandes (2022)
This research generally aims at analyzing the way a teacher education experience was co-constructed based on the Engaged Multiliteracy and how it can contribute to the decolonial education of educators who work with lesbian, gay, bisexual, transsexual, transgender, travestis, queer, intersex, asexual and pansexual people (LGBTQIAP+) within an educational programme of a non-governmental organization during the Coronavirus-19 pandemic. Our specific goals are: (1) to describe and analyze an ongoing process of teacher education based on the Engaged Multiliteracy that aims at contributing to the critical-collaborative education of educators who work at the NGO Casa 1; (2) to critically understand if and how the Decolonial Pedagogies can provide a teacher education process for educators who work at the NGO Casa 1 in order to co-construct an insurgent pedagogy of affirmation and reaffirmation of LGBTQIAP+ people; (3) to present suggestions for a proposal based on the development of an ongoing educational process of educators who teach at primary and secondary education throughout different fields of knowledge and that is based on the Engaged Multiliteracy and the Decolonial Pedagogies. Our guiding question is: how the Decolonial Pedagogies co-constructed based on the Engaged Multiliteracy can contribute to the process of teacher education of educators who work with the LGBTQIAP+ community? The data was produced during the ongoing teacher education process of a group of six educators who work at Casa 1, an NGO located in the city of São Paulo, during the second semester of 2021. This research is based on the theoretical-methodological foundations of Decoloniality (MIGNOLO, 2007, 2017; QUIJANO, 2005; SANTOS, MENESES, 2010; WALSH, 2019), Engaged Multiliteracy (LIBERALI, 2022) and Creative Chain (LIBERALI, 2018, 2021). As for the research methodology, we chose the Critical-Collaborative Perspective (MAGALHÃES, 2009, 2011, 2012) as it discusses the collective construction in the teacher education process departing from the transformation in the context those educators experience. The data analysis was conducted based on the analysis categories that grounds the critical reflection of the language (FREIRE, 1987; LIBERALI, 2021; SMYTH, 1992). The interpretation was made upon the interweaving of the Decolonial Studies, the Engaged Multiliteracy and the experience of the teacher education process. The results show that an ongoing teacher education process based on the Engaged Multiliteracy allows participants to co-construct other pieces of knowledge beyond the north-centered epistemologies and recover their knowledge throughout the teacher education process, considering their own bodies and experiences